HUBUNGAN PENYESUAIAN DIRI DENGAN KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Devi Cholivawati; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the independence of the child. Every child has different adaptations in adjusting themselves to their environment, where if the child has a good adjustment then the child will be able to face various problems that arise in his environment. This research aims to know the relationship of self-adjustment with the independence of children aged 5-6 years in TK Negeri Pembina 3 Kota Pekanbaru. This research is quantitative research with the type of correlation study. As for the population of this research of 100 children, the sample of this study was as much as 100 children. The data collection techniques used are observations. Data analysis techniques using Person Product Moment correlation technique. Based on the hypothesis test results obtained there is a positive and significant relationship between the self-adjustment with the independence of children aged 5-6 years in TK Negeri Pembina 3 Kota Pekanbaru. It can be known from the value of the correlation coefficient of rxy = 0.373 and the equivalent significance of 0.000 < 0.05. The level of relationship between self-adjusting to the independence of children aged 5-6 years in TK Negeri Pembina 3 Kota Pekanbaru belongs to the low category.Key Words: Self-Adjustment, Child Independence